2019
DOI: 10.1002/mpr.1774
|View full text |Cite
|
Sign up to set email alerts
|

Comparing outcomes: The Clinical Outcome in Routine Evaluation from an international point of view

Abstract: ObjectivesThe Clinical Outcome in Routine Evaluation–Outcome Measure (CORE‐OM) is a freely accessible self‐assessment questionnaire with a total of 34 items measuring the progress of psychological or psychotherapeutic treatments according to four scales (well‐being, problems, functioning, and risk). The CORE‐OM originated in the United Kingdom and has been translated into 54 languages and dialects. The aim of this study is to systematically compare the translated versions.MethodA total of 21 translations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…According to the instrument manual, the CORE-OM is not limited to a particular diagnosis [ 44 ]. Thus, the tool was applied to the case mix of our study with different baseline diagnoses.…”
Section: Methodsmentioning
confidence: 99%
“…According to the instrument manual, the CORE-OM is not limited to a particular diagnosis [ 44 ]. Thus, the tool was applied to the case mix of our study with different baseline diagnoses.…”
Section: Methodsmentioning
confidence: 99%
“…The original version in English has been translated into 54 languages and dialects (Zeldovich & Alexandrowicz, 2019). The Spanish version of the CORE-OM has shown good psychometric properties as a reliable and valid instrument to measure the progress of Spanishspeaking psychological therapy patients (Trujillo et al, 2016).…”
Section: Implications For Policymentioning
confidence: 99%
“…The original as well as translated versions of CORE‐OM have been subject to a number of psychometric studies examining aspects of its reliability and validity in different settings and samples (see, e.g., Evans et al, 2002; Zeldovich & Alexandrowicz, 2019). The results of these studies indicated high levels of internal consistency as well as stability (Evans et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As the main focus of the present study was to examine the functioning of the CORE‐OM using a Rasch model, it was of specific interest whether CORE‐OM was sufficiently unidimensional (one‐factorial) to be subjected to a Rasch analysis. It was clear from a recent systematic review and meta‐analysis examining the psychometric properties (including the factorial structure) of CORE‐OM (Zeldovich & Alexandrowicz, 2019) that the four domains of CORE‐OM do not map onto four separate factors. Instead, studies have reported one, two or three‐factorial solutions (for a review, see Zeldovich & Alexandrowicz, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation